Environmental Effects of Poultry Production in Abia State, Nigeria. (The NOUN Journal of Agricultural Research and Development (NJARD), 2025)
This study examined the environmental effects of poultry production in Abia State, Nigeria. A multi-stage random sampling technique was used to select 80 poultry farmers, and data were collected through structured questionnaires and oral interviews. Descriptive statistics and Tobit regression analysis were employed for data analysis. Results revealed that most farmers were middle-aged (62.5%), educated (85%), and experienced in poultry farming (83.5% with over 11 years’ experience). A majority had access to extension services (75%), credit facilities (87.5%), belonged to farmers’ organizations (58%), and lived in households of 4–6 members (43.7%). The major pollutants identified were microbial pathogens (20.4%), feed additives (19%), and wastewater (14.1%). Reported environmental effects included mosquitoes (12.4%), rats (11.1%), water contamination (12.1%), eutrophication (10%), noise (9.7%), pathogens (9%), flies (9.2%), drug residues (7.8%), land use constraints (9%), and dust (7.8%). Pollution control measures adopted included proper housing (34.6%), precision feed management (27.4%), and appropriate carcass disposal (23.2%). Socioeconomic factors significantly influencing the adoption of pollution management technologies were age, education, and access to extension services. Constraints to adoption included poor access to credit, inadequate extension services, illiteracy, high labor costs, expensive building materials, limited veterinary services, and weak organizational membership. The study recommends strengthening farmers’ access to extension services, credit, and educational programs, while encouraging participation in farmers’ organizations to enhance sustainable poultry waste management and mitigate environmental impacts.